Treatment Of Class 2-Hıgh Angle Cases Usıng The Combıned Actıvator-Occıpıtal Headgear - Müfide Dinçer (Galenos Yayinevi, 1989)
In this article, the use of a combined activator-occipital headgear appliances for treatment of 3 class 2, high angle cases at prepubertal period and results of the treatment are discussed. It was benefited from the orthodontic and orthopedic effects of functional and extraoral appliances separately and it was thought that undesirable effects of each appliances for cases could be eliminated by using the appliances together properly.